Selection of green solvents for organic photovoltaics by reverse engineering. Issue 2 (24th November 2021) - Wang, Jing; Rodriguez-Donis, Ivonne; Thiebaud-Roux, Sophie; Ibraikulov, Olzhas A.; Leclerc, Nicolas; Lévêque, Patrick; Gerbaud, Vincent; Kohlstädt, Markus; Heiser, Thomas
Abstract : We propose a new methodology involving reverse design of solvent molecules and evaluation of their molecular properties for a more efficient and less empirical selection of green solvents for organic photovoltaic device fabrication. Abstract : For a sustainable scale-up of solution-processed organic photovoltaic modules, the replacement of toxic solvents, generally used at laboratory scale, by alternative "green" solvents with a reduced impact on the environment and human health is a critical pre-requisite. Yet, because of the complex relationship between solvent properties and device performance, the selection of alternative solvents relies primarily on time-consuming and costly trial-and-error approaches. In this work we propose a new methodology involving prediction of molecular properties and reverse design for a more efficient and less empirical selection of green and bio-sourced solvents. The method is applied to four different donor–acceptor blends including polymers and small molecules. It allows to establish lists of possible alternative solvents ranked quantitatively by a global performance function encompassing all target properties. The actual performance of the highest ranked solvents are evaluated by using the selected solvents to elaborate photovoltaic devices and comparing the power conversion efficiencies with those obtained with devices processed from halogenated solutions. In all cases, the photovoltaic performances obtained with the alternative solvents are similar or superior to those of the standard devices, confirming the relevance of the new solvent selection method for solution-processed organic photovoltaic devices.